2016
DOI: 10.1210/en.2015-1574
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bisphenol A Exposure at Different Developmental Time Points in an Androgen-Sensitive Neuromuscular System in Male Rats

Abstract: The industrial plasticizer bisphenol A (BPA) is a ubiquitous endocrine disruptor to which the general human population is routinely exposed. Although BPA is well known as an estrogenic mimic, there have been some suggestions that this compound may also alter activity at the androgen receptor. To determine whether BPA does have antiandrogenic properties, we evaluated BPA effects in the spinal nucleus of the bulbocavernosus and dorsolateral nucleus, sexually dimorphic groups of motor neurons in the lumbar spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Given the above, BPA-induced fluctuations in the expression of VAChT as well as changes in the neurochemical characterization of cholinergic nerves observed during the present study may be the result of a direct impact of the toxin on muscles and neuromuscular junctions. Moreover, because the relaxatory effects of BPS have been reported in previous studies (Jones et al 2016 ), it stands to reason that the increase in the number cholinergic nerves noted after BPA administration is rather due to a suppression of acetylcholine release than an increase in the synthesis of this neuromediator.…”
Section: Discussionmentioning
confidence: 81%
“…Given the above, BPA-induced fluctuations in the expression of VAChT as well as changes in the neurochemical characterization of cholinergic nerves observed during the present study may be the result of a direct impact of the toxin on muscles and neuromuscular junctions. Moreover, because the relaxatory effects of BPS have been reported in previous studies (Jones et al 2016 ), it stands to reason that the increase in the number cholinergic nerves noted after BPA administration is rather due to a suppression of acetylcholine release than an increase in the synthesis of this neuromediator.…”
Section: Discussionmentioning
confidence: 81%
“…There is currently no direct evidence that BPA exposure is involved in ALS pathogenesis, yet motor neuron degeneration caused by environmental stressors may follow similar mechanisms and thus may be representative of sALS pathogenesis. BPA is a well characterized endocrine disruptor to which humans are ubiquitously exposed 34 . It is known to either activate or antagonize many different receptors such as estrogen receptors (ERs) α and β 35 , membrane-bound estrogen receptor GPR30, glucocorticoid receptors and androgen receptors (AR) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…BPA is a well characterized endocrine disruptor to which humans are ubiquitously exposed 34 . It is known to either activate or antagonize many different receptors such as estrogen receptors (ERs) α and β 35 , membrane-bound estrogen receptor GPR30, glucocorticoid receptors and androgen receptors (AR) 34 . BPA is structurally similar to 17 β -Estradiol (E2), the most prevalent estrogen in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have been undertaken to investigate the toxicity of BPA on juvenile populations and demonstrated potential harmful effects of BPA exposure on neuromuscular system ( Jones et al ., 2016 ), central nerve system and behavior ( Rebuli et al ., 2014 , 2015 ), adipogenicity and energy metabolism ( Rönn et al ., 2013 ), heart ( Ljunggren et al ., 2016 ), immune responses ( Ménard et al ., 2014 ), endocrine system ( Ahmed, 2016 ), the development of reproductive organs ( Delclos et al ., 2014 ) and liver ( Xia et al ., 2014 ). In most of these studies, however, bona fide signs of carcinogenicity could not be shown for low doses of BPA.…”
Section: Introductionmentioning
confidence: 99%